Expression and Role of INSL3 in the Fetal Testis - Ivell, Richard; Mamsen, Linn Salto; Andersen, Claus Yding; Anand-Ivell, Ravinder (Frontiers in Endocrinology, 2022)
Insulin-like peptide 3 (INSL3) is a small peptide hormone of the insulin-relaxin family which is produced and secreted by the fetal Leydig cells in the testes only. It appears to be undetectable in female fetuses. In the human fetus INSL3 synthesis begins immediately following gonadal sex determination at weeks 7 to 8 post coitum and the peptide can be detected in amniotic fluid 1 to 2 weeks later. INSL3 acts through a unique G-protein-coupled receptor, called RelaXin-like Family Peptide receptor 2 (RXFP2), which is expressed by the mesenchymal cells of the gubernacular ligament linking the testes to the inguinal wall. The role of INSL3 in the male fetus is to cause a thickening of the gubernaculum which then retains the testes in the inguinal region, while the remainder of the abdominal organs grow away in an antero-dorsal direction. This represents the first phase of testis descent and is followed later in pregnancy by the second inguino-scrotal phase whereby the testes pass into the scrotum through the inguinal canal. INSL3 acts as a significant biomarker for Leydig cell differentiation in the fetus and may be reduced by maternal exposure to endocrine disrupting chemicals, such as xenoestrogens or phthalates, leading to cryptorchidism. INSL3 may have other roles within the fetus, but as a Leydig cell biomarker its reduction acts also as a surrogate for anti-androgen action.